2008
DOI: 10.1111/j.1365-2702.2007.01998.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the knowledge, attitudes and practice patterns of operating room staff towards standard and transmission‐based precautions: results of a cluster analysis

Abstract: This study clearly profiles knowledge, attitudes and practice patterns of operating room staff, which may benefit healthcare educators in planning and developing appropriate educational programmes, may help organizations to provide a safe workplace climate and may aid healthcare workers to learn the importance of personal responsibility in preventing infectious disease transmission to patients, co-workers and even themselves. Relevance to clinical practice. To date, the only protection against infection is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
1
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 39 publications
5
67
1
7
Order By: Relevance
“…Askarian et al, showed no significant difference between the type and degree of specialty and the mean attitude score (19). In a study by Chan et al, on KAP level, no significant relation- ship was observed between the gender and work experience in the operating room (20). Moreover in their study, there was no significant difference in KAP, while in the current study the mean score of KAP showed no significant differences in gender.…”
Section: Discussioncontrasting
confidence: 47%
“…Askarian et al, showed no significant difference between the type and degree of specialty and the mean attitude score (19). In a study by Chan et al, on KAP level, no significant relation- ship was observed between the gender and work experience in the operating room (20). Moreover in their study, there was no significant difference in KAP, while in the current study the mean score of KAP showed no significant differences in gender.…”
Section: Discussioncontrasting
confidence: 47%
“…En effet, la plupart des participants sont des étudiants en médecine ou bien des infirmiers nouvellement recrutés. Dans ce sens, une étude chinoise a rapporté que les connaissances des professionnels non médicaux du bloc opératoire étaient également associées à un jeune âge, au sexe féminin, au niveau de formation, au grade et à l'expérience professionnelle (10). De même, les connaissances des infirmiers et des médecins étaient associées au suivi d'une formation et à une faible expérience professionnelle dans une étude réalisée en Suisse à Genève (11).…”
Section: Maîtrise Du Port De Gants à Usage Uniqueunclassified
“…Nurse is expected to perform all functions necessary for the total care of the patients. She must know how to protect others from contacting the disease, and she is responsible for disseminating prevention and control information to personnel, patients, their families and visitors Nursing students have a critical role to play in the prevention efforts and they are an important population to study their level of knowledge, attitudes, and behavior regarding infection control measures, and obtaining this information are useful for developing programs to improve their performance (13,14) . Therefore, the purpose of the present research is to study and analyze knowledge, attitude and practices towards infection control measures among nursing internship students and to explore the effect of nursing guidelines on their knowledge, performance and attitude in order to protect themselves and others from infection transmission.…”
Section: Introductionmentioning
confidence: 99%